Multiplexing curvature sensors using fibre segment interferometry for lateral vibration measurements - Kissinger, Thomas; Chehura, Edmon; James, Stephen W.; Tatam, Ralph P. (SPIE - International Society for Optics and Photonics, 2017)
Dynamic fibre-optic curvature sensing is demonstrated by interrogating chains of fibre segments, separated by broadband Bragg grating reflectors, using range-resolved interferometry (RRI). Four fibre strings, containing four fibre segments each of gauge length 20 cm, are attached to the opposing sides of a support structure and the resulting differential strain measurements allow inference of lateral displacements of a cantilever test object. Dynamic tip displacement resolutions in the micrometre range at an interferometric bandwidth of 21 kHz demonstrate the suitability of this approach for highly sensitive and cost-effective fibre-optic directional vibration measurements of smart structures. © (2017) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use only